Eko-Wisata Masyarakat Kampung Adat Segunung Jombang: Inisiasi Bangkit Di Tengah Pandemi Covid-19 - Silviana, Ika; Putri, Annisa Istiana Eka (Prodi Sosiologi Agama, 2022)
The presence of COVID-19 has shocked the entire world community. Each sector bears its own impact. The village community is no exception, which only works with their locality. The Kampung Adat Segunung community in Jombang Regency is also experiencing upheaval, especially in the economic sector. The area which has just been named a tourist village in 2019, must hold back the economy that is being pioneered by the community. Here, the hope of becoming an advanced tourist village must be restrained by the restrictions imposed by the government, as a prevention of the spread of the COVID-19 virus. Nevertheless, economic activity must continue, for the sake of meeting needs and achieving goals. Through the concept of rational choice from James S. Coleman, various steps taken by the Kampung Adat Segunung community are explained to maintain their economic growth. With a phenomenological approach, it explores the roles of actors in managing existing resources, and utilizes the norms they have as a basis for building stability. The Kampung Adat Segunung actors are driven by village tourism managers and MSME actors. The steps taken are to explore the potential of plantations and livestock to become superior products. So that it can support the potential of locality resources that have been managed, such as Omah Kopi, Omah Jamu, river tourism, etc.. The management of this potential is carried out with the principle of gotong royong, namely working together and highlighting the value of solidarity as the norm that is held. This practice is carried out not only by the main actors, but also collectively by the community.